Revisiting attenuation curves: the case of NGC 3351 - Calzetti, Daniela; Battisti, Andrew J.; Shivaei, Irene; Messa, Matteo; Cignoni, Michele; Adamo, Angela; Dale, Daniel A.; Gallagher, John S.; Grasha, Kathryn; Grebel, Eva K.; Kennicutt, Robert C.; Linden, Sean; et al. (The astrophysical journal, 2021)
Multiwavelength images from the far-UV (∼0.15 μm) to the submillimeter of the central region of the galaxy NGC 3351 are analyzed to constrain its stellar populations and dust attenuation. Despite hosting a ∼1 kpc circumnuclear starburst ring, NGC 3351 deviates from the IRX-β relation, the relation between the infrared-to-UV luminosity ratio and the UV continuum slope β that other starburst galaxies follow. To understand the reason for the deviation, we leverage the high angular resolution of archival near-UV-to-near-IR Hubble Space Telescope images to divide the ring into ∼60-180 pc size regions and model each individually. We find that the UV slope of the combined intrinsic (dust-free) stellar populations in the central region is redder than what is expected for a young model population. This is due to the region’s complex star formation history, which boosts the near-UV emission relative to the far-UV. The resulting net attenuation curve has a UV slope that lies between those of the starburst attenuation curve (Calzetti et al. 2000) and the Small Magellanic Cloud extinction curve; the total-to-selective attenuation value, (V) = 4.93, is larger than both. As found for other star-forming galaxies, the stellar continuum of NGC 3351 is less attenuated than the ionized gas, with E(B − V)star = 0.40 E(B − V)gas. The combination of the “red” intrinsic stellar population and the new attenuation curve fully accounts for the location of the central region of NGC 3351 on the IRX-β diagram. Thus, the observed characteristics result from the complex mixture of stellar populations and dust column densities in the circumnuclear region. Despite being a sample of one, these findings highlight the difficulty of defining attenuation curves of general applicability outside the regime of centrally concentrated starbursts.